KAJIAN KESESUAIAN LAHAN UNTUK TANAMAN DURIAN (Durio zibethinus Murr.) DI KEBUN BUAH MANGUNAN KECAMATAN DLINGO KABUPATEN BANTUL - Livi Takliviyah (FP AGRO 16 UMY 033, 2016)
Mangunan orchard is one area in Dlingo District, Bantul Regency which potential for the cultivation of durian (Durio zibethinus Murr.). From 2012 to 2013, the declining production of durian has occurred in this area. Accordingly, a study entitled â€œStudy of Land Suitability for Durian in Mangunan orchard, Dlingo District, Bantul Regencyâ€ conducted from Desember 2015 up to March 2016. The results showed that the Mangunan orchard actually quite suitable for cultivation of durian and have a class of land suitability for durian S2o, r-3, n- 1, e-1 with soil drainage, effective soil depth, cation exchangable capacity and slope as the limiting factors. The recommendation to increase durian production in the region are sub-surface soil tillage, organic matter application, terracing, contour parallel planting and crop cover planting.